Mapping synergies and trade-offs between energy and the Sustainable Development Goals. (January 2018) - Fuso Nerini, Francesco; Tomei, Julia; To, Long; Bisaga, Iwona; Parikh, Priti; Black, Mairi; Borrion, Aiduan; Spataru, Catalina; Castán Broto, Vanesa; Anandarajah, Gabrial; Milligan, Ben; Mulugetta, Yacob
Abstract The 2030 Agenda for Sustainable Development—including 17 interconnected Sustainable Development Goals (SDGs) and 169 targets—is a global plan of action for people, planet and prosperity. SDG7 calls for action to ensure access to affordable, reliable, sustainable and modern energy for all. Here we characterize synergies and trade-offs between efforts to achieve SDG7 and delivery of the 2030 Agenda as a whole. We identify 113 targets requiring actions to change energy systems, and published evidence of relationships between 143 targets (143 synergies, 65 trade-offs) and efforts to achieve SDG7. Synergies and trade-offs exist in three key domains, where decisions about SDG7 affect humanity's ability to: realize aspirations of greater welfare and well-being; build physical and social infrastructures for sustainable development; and achieve sustainable management of the natural environment. There is an urgent need to better organize, connect and extend this evidence, to help all actors work together to achieve sustainable development. The UN's Agenda for Sustainable Development has 17 goals with 169 targets for action across a range of issues, with access to sustainable energy for all being Goal 7. This Perspective analyses interlinkages between energy systems, Goal 7 and the other goals at the target level, identifying synergies and trade-offs between them.